Modern architecture in historic cities : policy, planning, and building in contemporary France - Loew, Sebastian; ebrary, Inc. (London : Routledge, Taylor & Francis Group, 1998)
Modern Architecture in Historic Cities illustrates why France has been so successful in combining conservation and modernity, and points to important lessons for other countries which can be drawn from the French experience. Beginning with an empirical review of particular events which have affected attitudes towards heritage in France, this book highlights the continuity in French thinking and the longstanding role of the French government as patron and leader. Planning, conservation and design control legislation are examined, highlighting the range of instruments available to government in order to influence results and enhance the role of the architectural profession.
1, Introduction -- 2, The history of planning and heritage protection in France -- 3, Control of new construction -- 4, Case studies -- 5, Clients and their agents -- 6, Participants in the control of development -- 7, Conclusions and lessons
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: 20. století; městská historická centra -- Francie; historické budovy -- Francie; ochrana památek -- Francie -- 20. století; moderní architektura -- Francie; urbanismus -- Francie -- 20. století; historical town centers -- France; historic buildings -- France; protection of monuments -- France -- 20th century; modern architecture -- France; city planning -- France -- 20th century; monografie; e-knihy online; monographs; e-books online